GS100-02-41: a new large H i shell in the outer part of the galaxy - Suad, Laura Andrea (2012)
Context. Massive stars have a profound effect on the surrounding interstellar medium. They ionize and heat the neutral gas, and with their strong winds they sweep up the gas, forming large H I shells. In this way, they generate a dense shell that provides the physical conditions for the formation of new stars. Aims. The aim of this study is to analyze the origin and evolution of the large H I shell GS 100-02-41 and its role in triggering star-forming processes. Methods. To characterize the shell and its environs, we carried out a multi-wavelength study. We analyzed the H I 21 cm line, the radio continuum, and infrared emission distributions. Results. The analysis of the H I data shows an expanding shell structure centered at (l,b) = (100°.6,-2°.04) in the velocity range from-29 to-51.7 km s -1. Taking into account noncircular motions, we infer for GS 100-02-41 a kinematical distance of 2.8 ± 0.6 kpc. Several massive stars belonging to Cep OB1 are located in projection within the large H I shell boundaries. The analysis of the radio continuum and infrared data reveals that there is no continuum counterpart of the H I shell. On the other hand, three slightly extended radio continuum sources are observed in projection onto the dense H I shell. From their flux density determinations we infer that they are thermal in nature. An analysis of the H I emission distribution in the environs of these sources shows a region of low emissivity for each of them, which correlates well morphologically with the ionized gas in a velocity range similar to the one where GS 100-02-41 is detected. Conclusions. Based on an energy analysis, we conclude that the origin of GS 100-02-41 could have been mainly caused by the action of the Cep OB1 massive stars located inside the H I shell. The obtained age difference between the H I shell and the H II regions, together with their relative location, lead us to conclude that the ionizing stars could have been created as a consequence of the shell evolution.